Artificial Intelligence in Mathematics Education: A Systematic Review of Opportunities, Challenges, and Pedagogical Implications - Ximenes, Salvador (PT. Riset Press International, 2025)
This systematic literature review is a study of the opportunities, difficulties, and educational implications of adopting artificial intelligence (AI) in mathematics education at the tertiary level in Timor-Leste. The review incorporates the international evidence collected based on 31 peer-reviewed studies published between 2016–2025 and presents it, given the realities of a higher education system in a developing country. These results demonstrate that AI, especially large language models like ChatGPT, has significant potential in terms of personalised instruction, customised feedback, and additional tutoring, which would solve the issue of teacher shortages and increase student interest. Despite these, there are still several obstacles, which include threats to academic integrity, algorithm biases, misalignment between cultures/languages, and a lack of infrastructure, particularly in rural areas. The review highlights the necessity of culturally responsive AI design and the development of ethical literacy among educators and learners, as well as the need to adapt to local pedagogical models to ensure equitable and effective application. It finds that AI can be a game changer in mathematics education in Timor-Leste, which should be implemented strategically, in a context-sensitive way, and through strong policies, infrastructure investment, and long-term teacher education leadership.